과학 교과와 연계된 통합 교육의 국내 연구 동향 분석 - 이효녕, 권영륜, 김성년, 손성호, 한욱신, 홍성구, 박병열, 전재돈 (교과교육학연구, 2014)
이 연구의 목적은 2009 개정 과학과 교육과정이 도입되기 전후 12년 동안 과학교과와 연계된 통합교육의 국내 연구는 어떻게 이루어져 왔는지 알아보는 것이다. 이 연구문제를 위해 2001년부터 2012년까지 학술지에 게재된 논문과 학위 논문 329편을 대상으로 그 동향을 분석하였다. 과학교육 연구 측면에서의 연구 동향을 알아보기 위해 이론적 배경을 통해 분석틀을 제작 하고 제작한 분석틀에 따라 연도별 연구 형태, 연구 방법, 연구 내용, 연구 대상을 분석하였다. 또 분석 대상 논문 중 교수·학습 프로그램을 개발한 논문을 개발한 분석틀에 따라 어떤 교과가 과학교과와 통합이 이루어졌는지, 교과의 조직방식, 통합의 조직요소, 학문이 연결되는 방식이 어떠한지를 분석하였다. 연구의 결과 과학교과와 연계된 통합교육의 연구 논문이 증가하였고, 연구 유형으로는 교수·학습 프로그램의 개발과 적용, 연구 주제는 교수·학습, 연구 대상으로는 초등학생이 많았다. 지난 12년 동안 개발된 교수·학습 프로그램을 분석한 결과, 과학교과와 통합을 가장 많이 한 교과는 미술이었고, 통합의 유형은 기여적 통합, 주제 중심 통합, 간학문적 통합이 가장 많았다. 본 연구의 결과를 바탕으로 학생들의 융합적인 소양의 배양을 위해 통합 과학 교육 교수학습 자료의 개발과 교사 연수프로그램의 개발 등을 제언하였다. The purpose of this study was to analyze the trend of the domestic research related to science integrated education carried out for the last 12 years before and after 2009 curriculum revision. The data was reviewed and collected from mater thesis, doctoral dissertations, and research articles published from 2001 to 2012. An analyzing framework was developed through literature reviews and content analysis of the previous studies. A total of 329 studies were selected and analyzed by year, type, content, and object of research. In addition, the method of organization of the subject, the elements of integration, the method of integration among different disciplines were additionally analyzed to find out the trend of integrated teaching-learning programs. The results indicated that the number of domestic studies related integrated science education have been increased from 2001 to 2012. The development and application of teaching-learning program as a type of research, the teaching and learning as a research topic, and elementary school students as a research object were more conducted compared to other studies. According to the analysis of teaching-learning programs, the subject matter integrated the most often with science was fine art. Theme-based integration approach was applied to the majority of type of integrated education. It is recommended that the development of teaching and learning materials and teacher training program in the integrated science education will be needed to foster students’ integrated scientific literacy. KCI Citation Count: 14